La determinación de la responsabilidad civil del auxiliar coactivo dentro de un procedimiento de ejecución coactiva - Chávez Rojas, Ricardo Alberto (2017)
This Master's Thesis aims to specify, if stipulated in Article 22 of the Single Ordered Text of Law No. 26979, of the Procedure of Coercive Execution, Supreme Decree No. 018-2008-JUS, on joint and several liability, In addition to the criminal and / or administrative for the coercive auxiliary, responds to the criterion of proportionality raised by the Law cited above. For our part, it is argued that there are no legal, social bases that allow us to continue to uphold the validity of this article unless it is proven negligent punishable by the coercive auxiliary, ie to act without authorization or against the provisions of the Coercive Executor, especially when in accordance with Article 2, subsection c) and d), Art. 3, Art. 4 and Art. 5 states that the Coercing Executor is the officer responsible for the Coactive Execution Procedure, and that the coactive assistant has the function of collaborating with the Executor. It is specified that in order to exercise the role of coercive executor, one must have a lawyer's title; In contrast, for the compulsory assistant, only the third year of university studies completed in Law, Accounting, Economics or Administration is required. Likewise, it is specified that the power of the public administration to protect its interests without recourse to the Judicial Branch or another State body is by the Principle of Self-Assessment and that the Co-operative Execution Procedure in Peru, is developed substantially under two norms: its own Law and Law 27444 of the General Administrative Procedure, while the latter places Coercive Execution as one of the means of enforcing execution, studying the issue of executivity, enforceability and Execution, and ending with a proposed amendment to Article 22 to regulate in a proportional way the participation of the coercive auxiliary, which is different from that of the coercive executor.